Comparative study to some semi numerical methods for solving nonlinear Wave-like Equations with variable coefficient - Mohanad Riyadh (University of Thi-Qar Journal of Science, 2019)
In this paper we solve the nonlinear wave-like Equations with variable coefficient by three Seminumerical methods, varational iteration method (VIM), homotopy perturbation method (HPM) andhomotopy analysis method (HAM). The solution obtained by these methods are Compared with the solutionobtained by Adomian decomposition method (ADM) and the exact solution [8].